Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd003935.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Repeat doses of prenatal corticosteroids for women at risk of preterm birth for improving neonatal health outcomes

Abstract: The short-term benefits for babies of less respiratory distress and fewer serious health problems in the first few weeks after birth support the use of repeat dose(s) of prenatal corticosteroids for women still at risk of preterm birth seven days or more after an initial course. These benefits were associated with a small reduction in size at birth. The current available evidence reassuringly shows no significant harm in early childhood, although no benefit.Further research is needed on the long-term benefits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(107 citation statements)
references
References 89 publications
1
101
0
4
Order By: Relevance
“…The combined use of these two corticosteroids has not been tested. A single repeat rescue course of antenatal betamethasone, given after the first completion of the course to women with threatened preterm labour, reduces RDS and other shortterm health problems, however, these effected are paralleled by the reduced birth weight [122,123].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…The combined use of these two corticosteroids has not been tested. A single repeat rescue course of antenatal betamethasone, given after the first completion of the course to women with threatened preterm labour, reduces RDS and other shortterm health problems, however, these effected are paralleled by the reduced birth weight [122,123].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…59,60,61 The results of ten randomized controlled trials, involving 4730 women and 5650 neonates have been summarized recent in a Cochrane review. 62 Treatment of women who remained at risk of preterm birth seven or more days after an initial course of antenatal corticosteroids with repeat dose(s) compared with no repeat treatment reduced the risk of infant respiratory distress syndrome (RR 0.83, 95%CI 0.75–0.91). In addition, serious infant morbidity was reduced by repeat dose(s) (RR 0.84, 95%CI 0.75–0.94).…”
Section: Timing Of Administrationmentioning
confidence: 99%
“…Likewise, the evidence for repeating treatment if delivery has not occurred within 7 days is mixed. Meta-analysis revealed that infants exposed to multiple steroid courses have lower risk of early respiratory morbidity, but tend to have reduced birth weight and head circumference 31. Current guidance advises against multiple courses, although a single additional rescue course may be appropriate when the first was before 26 weeks gestation 28…”
Section: Antenatal Interventionsmentioning
confidence: 99%